Response of unexplained chest pain to proton pump inhibitor treatment in patients with and without objective evidence of gastro-oesophageal reflux disease. Issue 11 (20th April 2011) - Kahrilas, Peter J; Hughes, Nesta; Howden, Colin W
Abstract : Introduction: Unexplained chest pain is potentially attributable to gastro-oesophageal reflux disease (GORD) or oesophageal motility disorders. Reflux chest pain may occur without heartburn. We explored the response of unexplained chest pain to proton pump inhibitor (PPI) therapy in randomised clinical trials (RCTs), differentiating patients with and without objective evidence of GORD. Methods: PubMed and Embase were systematically searched for RCTs that reported chest pain response to PPIs in patients who had had pH-monitoring and/or endoscopy to differentiate GORD-positive from GORD-negative subpopulations. Heterogeneity among studies was assessed using the Cochran Q and I 2 statistics, and a fixed effect model was applied. Possible publication bias was assessed by Egger's test. Results: Six RCTs met the inclusion criteria. All used 24 h pH monitoring and/or endoscopy to define GORD-positive patients and improvement in chest pain to define response (five used ≥50%; one used ≥20%). The therapeutic gain of >50% improvement with PPIs relative to placebo was 56–85% in GORD-positive and 0–17% in GORD-negative patients. The RR of >50% improvement in chest pain with PPI versus placebo was 4.3 (95% CI 2.8 to 6.7; p<0.0001) for GORD-positive and 0.4 (95% CI 0.3 to 0.7; p=0.0004) for GORD-negative patients. Concomitant heartburn varied among trials from being an exclusion criterion to being essentially concordant with GORD-positive status. Conclusions: Unexplained chest pain in patients with endoscopic or pH-monitoring evidence of GORD tends to improve, but not resolve, with PPI therapy, whereas GORD-negative patients have little or no response. Heartburn was a poor predictor of whether patients with chest pain were GORD-positive or GORD-negative by objective testing.